Persidangan Tertutup dalam Perkara Pidana Non-Kesusilaan: Problematika dan Urgensi Pembaharuan Hukum - Susilo, Erwin (PROGRESIF: Jurnal Hukum, 2025)
The principle of open court proceedings is a fundamental aspect of criminal procedural law to ensure a fair trial. However, there is a legal gap concerning the authority of judges to determine closed court sessions for cases containing elements of morality but not classified as morality-related cases. This study examines the legal issues and normative solutions to the ambiguity in the Indonesian Code of Criminal Procedure (KUHAP) regarding closed court proceedings in non-morality criminal cases. Using normative legal research methods and statutory, case, comparative, and conceptual approaches, this study compares the legal framework in Indonesia with the judicial system in Spain. The findings indicate that KUHAP does not provide clear guidelines for judges in determining closed court proceedings based on the substance of the evidence. Therefore, criminal procedural law reform is necessary to accommodate judicial flexibility in deciding closed trials while upholding the audi alteram partem principle. This reform aims to balance the principle of open court proceedings and the protection of parties' rights, ensuring that judicial decisions on the nature of court proceedings have a stronger legal foundation and can be consistently applied within Indonesia's criminal justice system.